(untitled) (Journal of Bangladesh Academy of Sciences, 2012)
The forecasting techniques for the prediction of nor’westers and associated winds and rainfall have been developed. Four linear multiple regression equations for computation of maximum gusty wind speed associated with nor’westers have been developed. The computed values of maximum gusty wind speed have statistically significant correlation with the actual maximum gusty wind speed. The regression equations have been verified with data of year (2005) and will be useful for the operational meteorologists for the computations of maximum gusty wind speed associated with nor’westers. Simple linear regression equations and linear multiple regression equations have also been developed for the statistical prediction of 24 hrs rainfall over Dhaka, country-averaged 24 hrs rainfall over Bangladesh and 24 hrs maximum rainfall over Bangladesh due to nor’westers. The correlation co-efficient corresponding to these regression equations are statistically significant. These equations have also been verified with the data of year 2005. Key words: Statistical techniques; Forecasting; Nor’westers; Bangladesh DOI: http://dx.doi.org/10.3329/jbas.v35i2.9416 JBAS 2011; 35(2): 125-140